Lessons From an Exploratory Qualitative Survey on Simulation Opportunities for Clinical Education in Speech-Language Pathology and Audiology in South Africa - Watermeyer, Jennifer; Kanji, Amisha (Teaching and learning in medicine, 2025)
Phenomenon : This study explored experiences of simulation-based clinical education in the Speech-Language Pathology and Audiology professions in South Africa, a Global South context where research on this topic is limited. In this context, the COVID-19 pandemic brought simulation to the forefront of clinical education as a training solution when in-person encounters were impossible. As these simulation-based training approaches gain traction, with continued use post-pandemic, it is important to understand how they are currently being used so that appropriate support can be offered to ensure their efficiency and success in the future. Approach : We distributed a survey to South African university departments offering Speech-Language Pathology and Audiology training, inviting participation from students across years of study and clinical educators. Data were collected between October 2022 and February 2023. Twelve responses were received: three from clinical educators and nine from students. We analyzed the responses using descriptive statistics and a domain summary approach. Findings : Simulated activities were implemented as options for clinical education in South African Speech-Language Pathology and Audiology (SLP/A) programs during the pandemic, albeit in a somewhat haphazard way depending on available resources, often with limited preparation or guidance. Some universities have continued using aspects of simulation training post-pandemic. Insights : Our findings, although preliminary, are somewhat consistent with Global North literature, particularly regarding barriers and challenges to implementing these approaches in clinical education. We offer suggestions for enhancing the support of simulation-based clinical education in our context.